Shear Strength Models for Steel Fibre Reinforced Concrete Beams: Current Scenario - Singh, Ranjodh; Singh, Harvinder (Civil Engineering Journal, 2021)
This review paper presents a comprehensive comparative analysis of various studies conducted on the shear strength of Self-compacting Concrete (SCC) and Normally Vibrated Concrete (NVC) in order to determine the sustainability and affordability of SCC as a construction material. Compaction is the main factor in concrete production. NVC needs compaction and vibration to remove the entrapped air which is both expensive and time-consuming. But SCC has flow ability and passing ability. Although SCC takes a greater amount of paste content, thereby raising the cost of building material, yet the use of such waste material as fly ash, silica, etc. comes in handy as paste content. Thus, the advantages offered by SCC in terms of increased strength as well as cost reduction makes it a highly desirable construction material. The review has selected the works of some eminent scholars on concrete and has analyzed them through individual as well as comparative perspective. A close analysis has helped filter out relevant works for the current study. This process of selection has proved helpful to include most standard works available in the review. Major findings have been enlisted at the end and ways to improve concrete behaviour have been suggested.Â Doi: 10.28991/cej-2021-03091661 Full Text: PDF